Paternal factors and adverse birth outcomes in Lanzhou, China - Jing Li; Jie Qiu; Ling Lv; Baohong Mao; Lei Huang; Tao Yang; Cheng Wang; Qing Liu (BMC, 2021)
Abstract Background Many maternal factors are known to be associated with adverse birth outcomes, but studies about paternal factors yielded inconsistent conclusions. The study was to assess whether paternal factors are associated with low birth weight (LBW), preterm birth (PTB), and small for gestational age (SGA). Methods A birth cohort study was conducted in 2010-2012 at the Gansu Provincial Maternity and Child Care Hospital, the largest maternity and childcare hospital in Lanzhou, China. Paternal age, ethnicity, educational level, height, weight, smoking, and drinking were collected. Birth outcomes and pregnancy complications were extracted from the medical records. Results During the study period, 10,121 participants were included; the overall prevalence of LBW, PTB, and SGA was 7.2, 9.9, and 7.8%, respectively. Paternal higher height (OR = 0.64 95%CI: 0.49, 0.83), higher weight (P for trend < 0.001), and higher BMI (P for trend < 0.001) could decrease the rate of LBW. Paternal higher education (OR = 0.55, 95%CI: 0.43, 0.71) and higher weight (P for trend < 0.001,) were associated with lower rate of PTB. Fathers who smoked more than 6 pack-years were associated with PTB (OR = 1.31, 95%CI: 1.07, 1.61). Paternal BMI > 23.9 kg/m2 (P for trend < 0.001,) and paternal education which above college (OR = 0.61, 95%CI: 0.50, 0.82) were associated with a lower rate of SGA. Conclusion Paternal low education is independently associated with PTB and SGA. Paternal heavy smoking is associated with PTB. Low paternal weight/BMI is independently associated with LBW, PTB, and SGA.